Pemanfaatan E-Book Interaktif "Kepemimpinan Khulafaur Rasyidin" Untuk Meningkatkan Pengetahuan Anak SD Kelas 6 - Novita Alamsyah; Ikhsan Ibrahim Ahmad; Aida Susilawati; Ani Nur Aeni (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Research entitled Utilization of Interactive E-books "Leadership of Khulafaur Rashidin" to Increase the Knowledge of Elementary School children in Grade 6 using the Design and Development (D&D) research method with the ADDIE development model explains the design and development of interactive e-book learning media on Khulafaur Rashidin’s leadership material in elementary school grade 6. The background of this research is to determine the composition of interactive E-book learning media, develop learning media, and collect responses and comments from experts and media users. They collected data using interview techniques, observation, distributing questionnaires, & literature study. Data analysis uses data reduction, data presentation, and research procedures. Reviews are grouped into several aspects, namely the quality of the content/material, language, & content. Responses from experts and users averaged 91% “Very good.” Experts & users also provide suggestions for evaluation material for designing and developing the developed learning media. Keywords: Interactive E-book, Khulafaur Rasyidin, Knewledge